Economic Efficiency as One of the Main Objectives of Auction Design - Kuśmierczyk, Paweł (Efektywność ekonomiczna jako jeden z głównych celów w przypadku aukcji, 2010)
Auctions are commonly used in case of narrow markets as the useful mechanisms which promote competition and help increase the revenues or lower the costs (in case of procurement). But many economists argue that an even more important objective of the auction design should be efficiency, which roughly means that the object is allocated to the participant, who values it the most. The paper analyzes the concept of economic efficiency and presents arguments why efficiency should be treated as an important objective of the auction design. It also shows that efficiency can be to high extent controlled through a careful design of the auction rules. Laboratory experiments serve as a useful tool which helps tailor those rules to meet the auctioneer's goals.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 73-82
Keywords: economic efficiency; Pareto efficiency; auctions; experiments